2011
DOI: 10.1161/hypertensionaha.111.176529
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Alters the Balance Between Vasoactive Compounds in Skeletal Muscle of Individuals With Essential Hypertension

Abstract: Abstract-The effects of physical training on the formation of vasodilating and vasoconstricting compounds, as well as on related proteins important for vascular function, were examined in skeletal muscle of individuals with essential hypertension (nϭ10). Muscle microdialysis samples were obtained from subjects with hypertension before and after 16 weeks of physical training. Muscle dialysates were analyzed for thromboxane A 2 , prostacyclin, nucleotides, and nitrite/nitrate. Protein levels of thromboxane synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
(63 reference statements)
4
39
3
Order By: Relevance
“…A large number of human (66,117,161) (136,352). It should be noted that exercise training also has been shown to increase levels of neuronal NOS (nNOS) (135,314,315,408).…”
Section: Enos Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…A large number of human (66,117,161) (136,352). It should be noted that exercise training also has been shown to increase levels of neuronal NOS (nNOS) (135,314,315,408).…”
Section: Enos Expressionmentioning
confidence: 99%
“…As described above, prostacyclin has been proposed to interact closely with NO in a manner where prostacyclin can compensate for a lack of NO and vice versa (40,291). Studies have shown that a period of exercise training increases the protein concentration of prostacyclin synthase and COX-1 in skeletal muscle tissue (135,175) although this has not been observed in all studies (161). In animal studies, training-induced improvements in endothelial dependent vasodilatation via bradykinine and acetylcholine are partly dependent on prostaglandins (86,87).…”
Section: Prostaglandinsmentioning
confidence: 99%
See 3 more Smart Citations